2017
DOI: 10.1080/02813432.2017.1333304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical accuracy of point-of-care urine culture in general practice

Abstract: ObjectiveTo assess the clinical accuracy (sensitivity (SEN), specificity (SPE), positive predictive value and negative predictive value) of two point-of-care (POC) urine culture tests for the identification of urinary tract infection (UTI) in general practice.DesignProspective diagnostic accuracy study comparing two index tests (Flexicult™ SSI-Urinary Kit or ID Flexicult™) with a reference standard (urine culture performed in the microbiological department).SettingGeneral practice in the Copenhagen area patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…The authors have previously examined the analytic performance of the Flexicult test using routinely submitted urine samples, 31 and the analytic performance of other POCT culture approaches have also been assessed. 19,[32][33][34] However, it was not possible to identify previous evaluations of intervention implementation to improve the management of UTI in terms of inappropriate antibiotic use, costs, resistance, and health outcomes. Holm et al have also found that POC culture was better at ruling in, rather than ruling out, a UTI diagnosis based on laboratory culture.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The authors have previously examined the analytic performance of the Flexicult test using routinely submitted urine samples, 31 and the analytic performance of other POCT culture approaches have also been assessed. 19,[32][33][34] However, it was not possible to identify previous evaluations of intervention implementation to improve the management of UTI in terms of inappropriate antibiotic use, costs, resistance, and health outcomes. Holm et al have also found that POC culture was better at ruling in, rather than ruling out, a UTI diagnosis based on laboratory culture.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Holm et al have also found that POC culture was better at ruling in, rather than ruling out, a UTI diagnosis based on laboratory culture. 34…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The reference, sending urine in boric acid for culture at the microbiological laboratory, has its flaws as previously described. 22 However, these flaws should have a similar effect on the two groups, since the distribution of growth and the resistance pattern did not differ significantly between groups.…”
Section: Discussionmentioning
confidence: 95%
“…Bias in the interpretation of the test was low as described previously. 22 GPs were blinded to the result of the reference at the time of deciding on treatment; POC test and reference were performed on the same portion of urine; the reference was adequate for ruling disease in or out and all data were included in the analysis. Allocation was concealed using sealed envelopes.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, results obtained in this study have highlighted the robustness of the MBS POCT for the detection of suspected UTIs and suggest how its rapidity, simplicity, and user-friendliness could represent key advantages for the clinical management of patients before a UTI is confirmed by culture-based laboratory methods. By comparison with available devices for UTI detection [33][34][35][36][37], it appears that the MBS POCT could place well among other culture-based devices thanks to its ability to combine short analytical time and high accuracy.…”
Section: Discussionmentioning
confidence: 99%